2018
DOI: 10.1021/acs.jafc.8b03410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Covalent Interaction with Chlorogenic Acid on the Allergenic Capacity of Ovalbumin

Abstract: Ovalbumin (OVA) is a major allergen in avian egg white. Here, we investigated the conjugation of OVA and chlorogenic acid (CHA) to reduce the allergenic capacity of OVA. OVA-CHA conjugate was characterized by SDS-PAGE, MALDI-TOF-MS, differential scanning calorimetry, and multispectroscopic methods. Sites of the OVA-CHA conjugate were identified by LC-MS/MS. CHA possibly conjugated with Lys20 and Lys17 in OVA, which resulted in the unfolding of OVA. ELISA and Western blot assay indicated that the OVA-CHA conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Reduced IgE-binding capacity Yuan et al (2019) Egg white proteins were preheated at 85°C for 30 min, then Alcalase (free or immobilized) was used for hydrolysis at pH 8 at 60°C from 10 to 250 min Reduced IgE-binding capacity Yang, Long et al (2017) Egg white in the presence or absence of egg yolk 2014; Hildebrandt et al (2008) antioxidant activity (Yang, Tu, Wang, Zhang, & Song, 2018). Both interactions with epigallo-catechin 3-gallate and chlorogenic acid reduced IgE-binding capacity of ovalbumin, due to the shielding of the linear IgE epitope (Lu et al, 2018;Ognjenović et al, 2014). Pulsed electric field treatment > 25 kV/cm (for 180 µs) or at 35 kV/cm for long time (>60 µs) was proven to reduce the IgE binding of ovalbumin, due to aggregate formation (Yang, Zhang et al, 2017).…”
Section: Processing Condition Allergenicity Change Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced IgE-binding capacity Yuan et al (2019) Egg white proteins were preheated at 85°C for 30 min, then Alcalase (free or immobilized) was used for hydrolysis at pH 8 at 60°C from 10 to 250 min Reduced IgE-binding capacity Yang, Long et al (2017) Egg white in the presence or absence of egg yolk 2014; Hildebrandt et al (2008) antioxidant activity (Yang, Tu, Wang, Zhang, & Song, 2018). Both interactions with epigallo-catechin 3-gallate and chlorogenic acid reduced IgE-binding capacity of ovalbumin, due to the shielding of the linear IgE epitope (Lu et al, 2018;Ognjenović et al, 2014). Pulsed electric field treatment > 25 kV/cm (for 180 µs) or at 35 kV/cm for long time (>60 µs) was proven to reduce the IgE binding of ovalbumin, due to aggregate formation (Yang, Zhang et al, 2017).…”
Section: Processing Condition Allergenicity Change Referencesmentioning
confidence: 99%
“…However, ultrasound combined with glycation has been reported to be effective in reducing its IgE‐binding ability as well as enhancing its antioxidant activity (Yang, Tu, Wang, Zhang, & Song, 2018). Both interactions with epigallo‐catechin 3‐gallate and chlorogenic acid reduced IgE‐binding capacity of ovalbumin, due to the shielding of the linear IgE epitope (Lu et al., 2018; Ognjenović et al., 2014). Pulsed electric field treatment > 25 kV/cm (for 180 µs) or at 35 kV/cm for long time (>60 µs) was proven to reduce the IgE binding of ovalbumin, due to aggregate formation (Yang, Zhang et al., 2017).…”
Section: Effect Of Processing On Allergenicity Of Eggmentioning
confidence: 99%
“…Stanic-Vucinic et al (2013) reported that chemical modification of β-LG is associated with structural and functional modification of proteins, which in turn may increase their allergenic potential by exposing hidden epitopes or creating new epitopes [78]. While the reaction of β-LG with lactose in milk showed increased allergenic activity [79], the allergenicity could be reduced by the covalent modification of ovalbumin [80] and the whey protein β-LG [7,81] with polyphenols in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This screening, in concert with further in vitro experiments revealed that procyanidin C1 and chlorogenic acid could potentially interact with Ara h 2 inducing conformational changes, which masked the IgE epitope [45]. Covalent interactions between chlorogenic acid and ovalbumin (OVA), the major allergen found in the egg white, also induced modifications in OVA conformation, resulting in the direct shielding of the linear IgE epitope, which attenuated allergic mechanisms [46]. Accordingly, histamine release experiments, showed that the basophil degranulation was inferior in human basophils sensitized with the OVA conjugated with chlorogenic acid when compared to OVA unconjugated, implying a decrease in the crosslinking of the FcεRI receptors via IgEallergen interaction [46].…”
Section: Food Allergiesmentioning
confidence: 94%
“…Covalent interactions between chlorogenic acid and ovalbumin (OVA), the major allergen found in the egg white, also induced modifications in OVA conformation, resulting in the direct shielding of the linear IgE epitope, which attenuated allergic mechanisms [46]. Accordingly, histamine release experiments, showed that the basophil degranulation was inferior in human basophils sensitized with the OVA conjugated with chlorogenic acid when compared to OVA unconjugated, implying a decrease in the crosslinking of the FcεRI receptors via IgEallergen interaction [46]. Also, the ability of phenolic compounds to bind to dietary allergen is pointed out as having a beneficial effect due to precipitation events [47].…”
Section: Food Allergiesmentioning
confidence: 99%